2013
DOI: 10.1016/j.molcel.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic ERK Activation Induced by Noise and Cell-to-Cell Propagation Regulates Cell Density-Dependent Proliferation

Abstract: The extracellular signal-regulated kinase (ERK) plays a central role in the signaling cascades of cell growth. Here, we show that stochastic ERK activity pulses regulate cell proliferation rates in a cell density-dependent manner. A fluorescence resonance energy transfer (FRET) biosensor revealed that stochastic ERK activity pulses fired spontaneously or propagated from adjacent cells. Frequency, but not amplitude, of ERK activity pulses exhibited a bell-shaped response to the cell density and correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
342
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(378 citation statements)
references
References 54 publications
34
342
2
Order By: Relevance
“…Currently, several lightinduced dimerization (LID) systems, in which photoactivatable proteins are dimerized by light in a reversible manner, are available. Among them, the cryptochrome 2 (CRY2) and cryptochrome-interacting basic helix-loop-helix1 (CIB1) pair has been widely used to control cell signaling through its lightinduced heterodimerization (11)(12)(13). CRY2 associates with its binding partner CIB1 upon exposure to blue light within a few seconds, and the complex is dissociated under a dark condition within several minutes (14).…”
mentioning
confidence: 99%
“…Currently, several lightinduced dimerization (LID) systems, in which photoactivatable proteins are dimerized by light in a reversible manner, are available. Among them, the cryptochrome 2 (CRY2) and cryptochrome-interacting basic helix-loop-helix1 (CIB1) pair has been widely used to control cell signaling through its lightinduced heterodimerization (11)(12)(13). CRY2 associates with its binding partner CIB1 upon exposure to blue light within a few seconds, and the complex is dissociated under a dark condition within several minutes (14).…”
mentioning
confidence: 99%
“…It was reported that rat kidney epithelial cells show stochastically pulsed MAPK activation in vitro, the frequency of which correlates with cell proliferation rate (Aoki et al, 2013). Interestingly, this pulsed MAPK activity is propagated to neighbor cells through EGF/ Ras/MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A similar propagation mechanism of cell proliferation may underlie clustering of cell division in zebrafish lens epithelium. Given that the frequency of MAPK activity pulses depends on cell density (Aoki et al, 2013), it would be interesting to investigate whether the level of cell proliferation depends on epithelial tension. Epithelial tension is transmitted through adherens junctions via E-cadherin (Borghi et al, 2012;Yonemura et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With this system, the construct between inverted terminal repeat sequences is randomly inserted into a host genome as a single structure by cotransfection with a DNA coding the specific transposase. Using this method, we have effectively obtained stable cell lines that express sufficient amounts of FRET biosensors (32,33), and to date we have not experienced any problems related to the recombination or destruction of the constructs.…”
Section: Generation Of Stable Cell Lines and Transgenic Mice Expressimentioning
confidence: 99%